Rural development in Bangladesh over four decades: Findings from Mahabub Hossain Panel Data and the way forward - Mohammad Abdul Malek; Aiko Kikkawa; Abul Kalam Azad; Yasuyuki Sawada (Asian Development Bank Institute (ADBI), 2022)
The Mahabub Hossain Panel Data (MHPD) was initiated in 1988 and maintained by and named after the late Dr. Mahabub Hossain, a well-known agricultural and development economist who led a number of reputed organizations in Bangladesh (Bangladesh Institute of Development Studies and BRAC) and in the region (International Rice Research Institute). This background report portrays the historical context, sampling evolution, survey structure and methodology, and academic and policy contributions of the MHPD with some lessons learned for the next step forward. The MHPD has tracked rural households for a period of over three decades (1988-2014) with five waves of household surveys covering over 2,800 households and has collected a wide range of information on household composition, schooling of household members, assets, cropping intensity and patterns including cost and return, employment and income, consumption, participation in different government and nongovernment programs. To produce this document, we reviewed several books and journal articles authored by Mahabub Hossain and related academic papers and documents and collated information on MHPD, including (i) mapping out information on past and ongoing panel or cross-sectional household survey data series in Bangladesh; (ii) undertaking the review of all past rounds of MHPD survey documents, such as survey implementation plans, questionnaires, codebooks, databases, and processed data; (iii) consulting relevant stakeholders, including the past implementers of the surveys and the users of the data as needed to validate documented information; (iv) taking stock of the contribution of MHPD to academic literature and policy development; and (v) drawing a number of lessons learned for future data collection and policy making. The report aims to i) serve as a comprehensive reference document for scholars and policymakers who wish to understand MHPD for possible use in their research; ii) provide a comprehensive baseline from which we can consider ways to enhance MHPD further to continue contributing to understanding the economic and social issues of today and near future. By compiling all associated research work based on MHPD, the report also offers a historical landscape of Bangladesh's social and economic development and a credible explanation for the Bangladesh development model for global comparison.
Keywords: C81; O18; Q12; Z18; 330; Bangladesh; rural development; household panel data; evidence-based policy making (EBPM)